Irradiation with carbon ions effectively counteracts hypoxia-related radioresistance in a rat prostate carcinoma - Glowa, Christin; Bendinger, Alina L.; Euler-Lange, Rosemarie; Peschke, Peter; Brons, Stephan; Debus, Jürgen; Karger, Christian (International journal of radiation oncology, biology, physics, 2024)
Purpose - Hypoxia in tumors is associated with increased malignancy and resistance to conventional photon radiation therapy. This study investigated the potential of particle therapy to counteract radioresistance in syngeneic rat prostate carcinoma. - Methods and Materials - Subcutaneously transplanted R3327-HI tumors were irradiated with photons or carbon ions under acute hypoxic conditions, induced by clamping the tumor-supplying artery 10 min before and during irradiation. Dose-response curves were determined for the endpoint “local tumor control within 300 days” and compared with previously published data acquired under oxic conditions. Doses at 50% tumor control probability (TCD50) were used to quantify hypoxia-induced radioresistance relative to that under oxic conditions and also to quantify the increased effectiveness of carbon ions under oxic and hypoxic conditions relative to photons. - Results - Compared with those under oxic conditions, TCD50 values under hypoxic conditions increased by a factor of 1.53 ± 0.08 for photons and by a factor of 1.28 ± 0.06 for carbon ions (oxygen enhancement ratio). Compared with those for photons, TCD50 values for carbon ions decreased by a factor of 2.08 ± 0.13 under oxic conditions and by a factor of 2.49 ± 0.08 under hypoxic conditions (relative biological effectiveness). While the slope of the photon dose-response curves increased when changing from oxic to hypoxic conditions, the slopes were steeper and remained unchanged for carbon ions. - Conclusions - The reduced oxygen enhancement ratio of carbon ions indicated that the required dose increase in hypoxic tumors was 17% lower for carbon ions than for photons. Additionally, carbon ions reduced the effect of intertumor heterogeneity on the radiation response. Therefore, carbon ions may confer a significant advantage for the treatment of hypoxic tumors that are highly resistant to conventional photon radiation therapy.
Gesehen am 19.03.2025